Single Cell Meta-Analysis of Endothelial to Mesenchymal Transition (EndMT) in Glucose Metabolism of the Digestive Diseases - Zhou, Qiao; Zhang, Xin; Tong, Xia; Tang, Chuang; Chen, Xin; Peng, Ling; Xia, Xiangen; Zhang, Lanlan (Frontiers in Molecular Biosciences, 2022)
Background: The role of endothelial to mesenchymal transition (EndMT) in digestive diseases is less explored, and the involvement of metabolism in EndMT is unknown. Objective: The purpose of this study is to determine the function of EndMT in digestive illnesses and to characterize its metabolic status. Method： We extracted single-cell data from the GEO database to identify subpopulations of EndMT in digestive organs such as premalignant lesions and cancer in the stomach, intestine, and pancreas. Results: Using single-cell RNA sequencing in digestive diseases, we generated a single-cell atlas from tissues of patients spanning a cascade of premalignant lesions and cancer. We then constructed a single-cell network underlying cellular and molecular characteristics of endothelial cells（ECs）across different lesions and identiﬁed essential genes associated with EndMT in the early-malignant lesion and cancer lesions. The analysis of ECs revealed that EndMT activated a large number of metabolic signaling pathways in ECs, and further analysis of premalignant lesions and cancer suggested that glucose metabolism exhibited an increase from premalignant lesions and reached a maximum in cancer tissue. Finally, it was established that RAC1, INSR1and LDHA might be employed as a predictive marker for the progression of premalignant lesions to cancer-related to glucose metabolism. Conclusion: We identified EndMT's participation in the GI ECs and defined its metabolism for the first time, highlighting the critical significance of glucose metabolism in disease. By screening for target genes, we identified a number of targets that are useful for predicting premalignant lesions to cancer.